1985
DOI: 10.1002/j.1460-2075.1985.tb03854.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the coding region for a second Epstein-Barr virus nuclear antigen (EBNA 2) by transfection of cloned DNA fragments.

Abstract: Cell lines were established by co-transfection of cloned M-ABA Epstein-Barr virus (EBV) DNA fragments with plasmids conferring resistance to dominant selective markers. A baby hamster kidney cel line carrying the HindIlI-I1 fragment exhibits a nuclear antigen of 82 000 daltons, serologicaily defined as EBV-determined nuclear antigen (EBNA) 1. Furthermore, a Rat-i cell line transfected with DNA of the clone pM 780-28 containing three large internal repeats (Bgl-U) and the adjacent BgMl-C fragment expresses a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…It is now well established that the BamHI WYH region of the EBV genome encodes a protein localized to the nucleus of the EBV-infected cell, which has been designated EBNA2 (Dillner et al, 1985;Hennessy & Kieff, 1985;Mueller-Lantzsch et al, 1985 ;Rowe et al, 1985;Rymo et al, 1985). It is also clear that the long rightward open reading flame beginning in the BamHI Y fragment of EBV DNA (BYRFI, see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well established that the BamHI WYH region of the EBV genome encodes a protein localized to the nucleus of the EBV-infected cell, which has been designated EBNA2 (Dillner et al, 1985;Hennessy & Kieff, 1985;Mueller-Lantzsch et al, 1985 ;Rowe et al, 1985;Rymo et al, 1985). It is also clear that the long rightward open reading flame beginning in the BamHI Y fragment of EBV DNA (BYRFI, see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Four other EBV-determined, transformation-specific nuclear proteins, EBNA2, EBNA3, EB NA4 and EBNAS, have been defined by immunological 0000-7676 © 1987 SGM (Dillner et al, 1986;Hennessy & Kieff, 1983;Hennessy et al, 1985Hennessy et al, , 1986Sculley et al, 1984;Strnad et al, 1981). DNA-mediated gene transfer experiments have demonstrated that the coding sequence for EBNA2 is within the BamHI WYH region of the EBV genome (Mueller-Lantzsch et al, 1985;Rowe et al, 1985;Rymo et al, 1985). The rightward long open reading frame in the BamHI Y and H fragments (BYRFl ; Baer et al, 1984) contains EBNA2-specific sequence information.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently the cloning of DNA fragments from the non-homologous regions of the M-ABA (a B95-8-1ike isolate) (Polack et al, 1984) and the Jijoye (Adldinger et al, 1985) virus genomes has provided probes which can distinguish all EBV isolates as either 'type A' (B95-8-1ike) or 'type B' (Jijoye-like) in the BarnHI WYH region. These differences in fact stem from sequence divergence within the open reading frame encoding the nuclear antigen EBNA 2 (Hennessy & Kieff, 1985;Dillner et al, 1985 ;Rymo et al, 1985 ;Muller-Lantzsch et al, 1985). Thus the EBNA 2 type B protein found in Jijoye and in AG876 cells is significantly smaller (75K tool.…”
Section: Introductionmentioning
confidence: 99%
“…These include a species originally termed EBNA (Epstein-Barr nuclear antigen). In fact, three separate nuclear proteins are now recognized: EBNA1 (the original), EBNA2 and EBNA3 (Mueller-Lantzsch et al, 1985 ;Rymo et al, 1985;Hennessy et al, 1985). Yates et al (1985) and Lupton & Levine (1985) showed that EBNA1 alone is sufficient for maintenance of OriP plasmids, so that plasmids carrying OriP and an active EBNA1 gene replicate in many cell types not carrying EBV.…”
Section: Replication Of Epstein-barr Virus Dna In Latently Infected Cmentioning
confidence: 99%